Breaking Barriers in English Writing: Pedagogical Shifts under the Merdeka Curriculum in Vocational Education - Elfiyanto, Sonny; Nasihah, Durotun; Romadhon, Muhammad Galuh Elga; Umeki, Riko (Journal of English Teaching and Learning Issues, 2025)
This research aims to explore the implementation of English writing teaching within the curriculum framework of Merdeka Curriculum at Indonesian vocational high schools, focusing on understanding, classroom practice, and challenges faced by teachers in implementing project-based, student-centered principles. Adopting a concurrent, transformative mixed-methods design, data were obtained from thirteen English teachers in Malang, East Java, through qualitative interviews and quantitative surveys to reveal their perceptions and practices. The results indicate that a gap between the intended flexible curriculum, centered on differentiated instruction, student choice, and active engagement, and what is actually happening in classrooms has continued to persist. Instructors have a partial understanding of such pedagogical facts. However, the practice is suppressed by students' varying writing proficiency levels, scarce learning materials, inadequate professional training, and limited support from the school. Merdeka Curriculum: a source of hope. Nevertheless, as much as Merdeka Curriculum offers an inspiring vision of pedagogical transformation. Structurally, there are impediments to its effective realization in the world of vocational education. Continued systemic support and increased pedagogical alignment are necessary to achieve a more meaningful curricular change. Empowering teacher initiative, developing teacher collaboration, and providing continuous professional development are essential to improve writing instruction in trade or technical schools. The study provides policymakers, administrators, and curriculum developers with the knowledge to simplify support systems, enabling English teachers to implement Merdeka Curriculum in the writing classroom fully.